2015
DOI: 10.2146/ajhp140139
|View full text |Cite
|
Sign up to set email alerts
|

How mobile devices are changing pharmacy practice

Abstract: Am J Health-Syst Pharm. 2015; 72:494-500

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Mobile apps can be broadly defined as downloadable or web‐based software programs that operate on a mobile device platform (eg, smartphone, tablet) . In recent years, the prevalence of these apps in medicine has grown substantially, particularly within the area of pharmacy practice and the provision of drug information .…”
Section: Additional Considerations For Unique Electronic Resources Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile apps can be broadly defined as downloadable or web‐based software programs that operate on a mobile device platform (eg, smartphone, tablet) . In recent years, the prevalence of these apps in medicine has grown substantially, particularly within the area of pharmacy practice and the provision of drug information .…”
Section: Additional Considerations For Unique Electronic Resources Inmentioning
confidence: 99%
“…15,31 In recent years, the prevalence of these apps in medicine has grown substantially, particularly within the area of pharmacy practice and the provision of drug information. 31 This growth is not surprising considering the many proposed benefits of these apps, such as improved efficiency, enhanced clinical decision making, and the ability to get real-time information at the bedside more rapidly than before. However, much like other types of medical resources, health care professionals must ensure the information from these apps are evidence-based and safe to apply in patient care.…”
Section: Mobile Medical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that patients using digital health technologies are more engaged and informed about their health. [2][3][4][5] These patients display greater motivation and capability to improve their health, and feel better equipped to have intelligent discussions with health care providers. 3,4 Although a multitude of technological products are available, the health care industry has to determine how to shrink the gap between technological advancement and current health care reality.…”
mentioning
confidence: 99%
“…Digital health is challenging the health care industry, an industry that historically has been slow to adopt new technology and is encumbered by significant regulatory barriers. 3,[6][7] Although the pharmacy profession has not historically been early adapters of technology, patients trust and frequently interact with pharmacists, making pharmacists an excellent patient resource in this era of technological advancement. The purpose of this article is to generate awareness of the many facets of digital health, furthermore empowering pharmacists to become leaders of digital health solutions within and beyond their practice settings.…”
mentioning
confidence: 99%